1997
DOI: 10.1046/j.1365-2923.1997.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning in a problem‐based medical curriculum: students' conceptions

Abstract: The purpose of this study was to examine students' conception of their learning in a problem-based learning medical curriculum. A multiple case study design was used with two units of analyses: two PBL lab groups; and 15 individual students within each lab group. Data collected included weekly journals by students, video-tapes of PBL sessions, focus group interviews with students, two open-ended questionnaires completed by students, and interviews with the PBL tutors. Three thematic categories of students' con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Students also could be achieved the goals of self-directed learning, motivation, interaction among group members, communication, coordination, teamwork, and respect through PBL [51] . Furthermore, more than one literature review seems to support this view of point [37,38] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Students also could be achieved the goals of self-directed learning, motivation, interaction among group members, communication, coordination, teamwork, and respect through PBL [51] . Furthermore, more than one literature review seems to support this view of point [37,38] .…”
Section: Discussionmentioning
confidence: 91%
“…[36] . However, the majority of the literature supports the viewpoint that the PBL method enables the development of effective self-directed learning skills that encourage students to be responsible for their professional growth [25,37,38] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many reports claimed that PBL not only helps students in the acquisition of content knowledge but also promotes their learning in dealing with complex problems, enriches their learning of basic science information, leads them to self-directed life-long learning, improves the effectiveness of their communication, cooperative study and self-evaluation skills, and allows them to adapt to changes (Albanese &Mitchell, 1993;Caplow et al, 1997;Schmidt et al, 2006;Schmidt et al, 2011) However, some studies were not in favour of PBL (Bowman et al, 2005). A few might feel that PBL is a threat to basic science (particularly anatomy) education since the fundamentals of the disciplines may be neglected and there exists many problems.…”
Section: Introductionmentioning
confidence: 99%
“…Student perceptions of learning in tutorials have mostly been examined by using written materials, usually questionnaire surveys 10,13 , 18 . The few extant interview studies 19–21 addressed general outlines and specific situations. Steinert's study of student perceptions of small‐group learning in a non‐PBL curriculum 21 revealed a predilection for active student participation, group interaction and positive group atmosphere.…”
Section: Introductionmentioning
confidence: 99%